2014
DOI: 10.1007/s10495-014-0983-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term blue light exposure induces RGC-5 cell death in vitro: involvement of mitochondria-dependent apoptosis, oxidative stress, and MAPK signaling pathways

Abstract: The mechanism of blue light-induced retinal ganglion cell (RGC) injury is poorly understood. In this study, we established a patented light-emitting diode-based system to study the effects of long-term blue light exposure under culture conditions on RGC-5 cells. Long-term blue light exposure significantly reduced cell viability in a time-dependent manner and induced apoptosis and necrosis in RGC-5 cells. Long-term blue light exposure marked an increase in the expression of Bax and active Caspase-3 (p17), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 30 publications
4
44
0
Order By: Relevance
“…Alteration of ROS production may represent an important mechanism for zerumbone-mediated regulation of cellular behaviors. Substantial ROS has been found to activate MAPK signaling cascades [28]. Consistent with suppression of ROS production, we found that zerumbone treatment resulted in a significant reduction in the phosphorylation of p38 and JNK MAPKs.…”
Section: Discussionsupporting
confidence: 84%
“…Alteration of ROS production may represent an important mechanism for zerumbone-mediated regulation of cellular behaviors. Substantial ROS has been found to activate MAPK signaling cascades [28]. Consistent with suppression of ROS production, we found that zerumbone treatment resulted in a significant reduction in the phosphorylation of p38 and JNK MAPKs.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to ROS generation, BL irradiation activates mitogen-activated protein kinases (MAPKs), which play an important role in cell survival and apoptosis. Mitochondria-dependent apoptosisrelated pro-apoptotic proteins, such as Bax and caspase-3, are activated by BL-emitting diode light (BLL) irradiation via the c-Jun N-terminal kinase (JNK) and p38 pathways in RPE and retinal ganglion cells [8]. Moreover, the phosphatidylinositol 3-kinase (PI3K)/Akt and nuclear factor erythroid 2-related factor 2 (Nrf2)-dependent anti-oxidative pathways are components of the defense system of RPE cells [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their high imaging quality, these lock-in methods commonly require acquisition of the time-varying fluorescence intensity signal over several modulation cycles and the pixel-by-pixel processing of dataset; thus, an image acquisition time of a few minutes is required to obtain a background-free fluorescence image. This time-consuming approach may hamper the cell viability owing to the long-term exposure to a strong excitation light [7].…”
Section: Introductionmentioning
confidence: 99%